2013
DOI: 10.3945/ajcn.112.050021
|View full text |Cite
|
Sign up to set email alerts
|

DHA supplementation and pregnancy outcomes

Abstract: A supplement of 600 mg DHA/d in the last half of gestation resulted in overall greater gestation duration and infant size. A reduction in early preterm and very-low birth weight could be important clinical and public health outcomes of DHA supplementation. This trial was registered at clinicaltrials.gov as NCT00266825.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
244
4
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(269 citation statements)
references
References 20 publications
(27 reference statements)
14
244
4
4
Order By: Relevance
“…However, because the fetal liver is not capable of making sufficient DHA (6,56) and because DHA is critical for cells of the central nervous system for forming membrane phospholipids required for neurogenesis and synaptogenesis (8,(57)(58)(59), a maternal deficit could have significant consequences for the fetus and offspring. In addition, maternal DHA supplementation has been associated with improved fetal growth (60).…”
Section: Discussionmentioning
confidence: 99%
“…However, because the fetal liver is not capable of making sufficient DHA (6,56) and because DHA is critical for cells of the central nervous system for forming membrane phospholipids required for neurogenesis and synaptogenesis (8,(57)(58)(59), a maternal deficit could have significant consequences for the fetus and offspring. In addition, maternal DHA supplementation has been associated with improved fetal growth (60).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, hydrophobic extracts of plasma and breast tissue were separated into PLs and TAGs by solid-phase chromatography (37). After transmethylation with boron trifluoride-methanol, fatty acid methyl esters were isolated and analyzed by gas chromatography using a Varian 3900 (Agilent Technologies) with helium as the carrier gas and reported as weight percent of total fatty acids as previously described (38).…”
Section: Fatty Acidsmentioning
confidence: 99%
“…In a double blind RCT including 350 women receiving either 600mg/d DHA or placebo, the authors found that supplementation during the last half of gestation resulted in overall greater gestation duration and infant size [8].…”
Section: Dha and Fetal Growthmentioning
confidence: 99%
“…As the need for DHA is increased during the third trimester, a daily supplementation could be recommended [7]. Many studies have reported the benefits of an adequate DHA status during pregnancy and lactation [8,9]. The clinical importance of such effects on infant health has not been fully elucidated and is controversial.…”
Section: Introductionmentioning
confidence: 99%